Allelic Polymorphism Determines Surface Expression or Intracellular Retention of the Human NK Cell Receptor KIR2DL5A (CD158f) - Cisneros, Elisa; Estefanía, Ernesto; Vilches, Carlos (Frontiers in Immunology, 2017)
KIR2DL5 (CD158f) is the most recently identified inhibitory member of human Killer-cell Ig-like Receptors (KIR), which enable NK cells to sense self HLA. Unlike KIR2DL1–3, recognising HLA-C allotypes through Ig-like domains of the D1-D2 type, KIR2DL5 shares a D0-D2 configuration with KIR2DL4, and its ligands have not been identified. KIR2DL5 is encoded by two paralogous genes displaying copy-number variation and allelic polymorphism – KIR2DL5A and KIR2DL5B. UP-R1 mAb, raised against the common allele KIR2DL5A*001, enables specific KIR2DL5 detection. However, not every KIR2DL5+ individual has NK cells staining with UP-R1, discrepancy explained in part by epigenetically silent KIR2DL5B alleles with a distinctive substitution in a promoter RunX-binding site. Furthermore, we show here that the transcribed allele KIR2DL5A*005, second most common of its locus, fails to confer NK cells UP-R1 reactivity, phenotype explained by inefficacious transport of its product to the cell surface. Two amino acid substitutions distinguish the KIR2DL5A*005 and *001 coding regions. Western blot, flow cytometry and confocal microscopy analyses of cells transfected with tagged constructs demonstrate that a serine substitution for glycine 174, conserved in most KIR, is mainly responsible for KIR2DL5A*005 intracellular retention, and it also affects mAb recognition. In contrast, substitution of aspartate for asparagine 152 has only a minor effect on surface expression, despite destroying an otherwise conserved N-glycosylation site. Our results help to explain the variable expression profile of KIR2DL5+ subjects, and indicate that functional polymorphisms in both its promoter and its coding regions are critical for understanding the KIR2DL5 role in immunity, and its importance for human health.